SCALE, PLACE AND SOCIAL MOVEMENTS: STRATEGIES OF RESISTANCE ALONG INDIA’S NARMADA RIVER - Basu, Pratyusha (REVISTA NERA, 2012)
This paper focuses on the struggles being waged by the Narmada Bachao Andolan, a rural social movement opposing displacement due to dams along India’s Narmada River. Building a comparison between two major anti-dam struggles within the Andolan, around the Sardar Sarovar and Maheshwar dams, this study seeks to show that multi-sited social movements pursue a variety of scale and place-based strategies and this multiplicity is key to the possibilities for progressive change that they embody. The paper highlights three aspects of the Andolan. First, the Andolan has successfully combined environmental networks and agricultural identities across the space of its struggle. The Andolan became internationally celebrated when its resistance led to the World Bank withdrawing funding for the Sardar Sarovar dam in 1993. This victory was viewed as a consequence of the Andolan’s successful utilization of transnational environmental networks. However, the Andolan has also intervened in agrarian politics within India and this role of the Andolan emerges when the struggle against the Maheshwar dam is considered. Second, this paper examines the role played by the Andolan in building a national movement against displacement. Given that India’s Supreme Court gave permission for the continued construction of the Sardar Sarovar dam in 2000, the power of the state to push through destructive development projects cannot be underestimated. The national level thus remains an important scale for the Andolan’s struggle leading to the formation of social movement networks and the construction of collective identities around experiences of rural and urban displacement. Third, this paper reflects on how common access to the Narmada river also provides a material basis for the formation of a collective identity, one which can be used to address the class divisions that characterize the Andolan’s membership. Overall, the paper aims to contribute to the study of social movements by showing how attachments to multiple geographies ensure that a movement’s potential futures always exceed the nature of its present forms of resistance.